2018
DOI: 10.1161/jaha.117.008145
|View full text |Cite
|
Sign up to set email alerts
|

Protective Roles of Interferon‐γ in Cardiac Hypertrophy Induced by Sustained Pressure Overload

Abstract: BackgroundA clear understanding of the molecular mechanisms underlying hemodynamic stress‐initiated cardiac hypertrophy is important for preventing heart failure. Interferon‐γ (IFN‐γ) has been suggested to play crucial roles in various diseases other than immunological disorders by modulating the expression of myriad genes. However, the involvement of IFN‐γ in the pathogenesis of cardiac hypertrophy still remains unclear.Methods and ResultsIn order to elucidate the roles of IFN‐γ in pressure overload–induced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 49 publications
4
36
0
Order By: Relevance
“…Although IFN- is implicated in immune and inflammatory responses as a component of the Th1 response, its increased expression has been shown to exert contrasting effects; promote cardiovascular dysfunction or mediate cardioprotective effects [55][56][57][58][59][60]. However, unlike in other studies [56][57][58][59][60], changes in IFN- levels did not correlate with suppression of cardiac hypertrophy in the sac/val-treated ZO rats. IL-4 levels were also elevated in ZOSV, but not in other treatment groups, suggesting that increased IL-4 levels in this treated group might have contributed to the higher impact of sac/val over val in ZO rats.…”
Section: Discussionmentioning
confidence: 57%
“…Although IFN- is implicated in immune and inflammatory responses as a component of the Th1 response, its increased expression has been shown to exert contrasting effects; promote cardiovascular dysfunction or mediate cardioprotective effects [55][56][57][58][59][60]. However, unlike in other studies [56][57][58][59][60], changes in IFN- levels did not correlate with suppression of cardiac hypertrophy in the sac/val-treated ZO rats. IL-4 levels were also elevated in ZOSV, but not in other treatment groups, suggesting that increased IL-4 levels in this treated group might have contributed to the higher impact of sac/val over val in ZO rats.…”
Section: Discussionmentioning
confidence: 57%
“…46 Kimura et al reported protective roles of IFN-γ in the pathogenesis of pressure overload-induced cardiac hypertrophy and demonstrated that bone marrow (BM)-derived CD68+ macrophages are a source of IFN-γ and infiltrating immune cells including macrophages appear to be responsible for intracardiac IFN-γ expression. 47 However, Liu et al reported that Bacillus Calmette-Guerin (BCG) and TLR4 agonists prevented pathological cardiac hypertrophy and revealed that their protective actions are mediated by IFN-γ secreted from cardiomyocytes in the left ventricle. 48 In Angioten II-induced cardiac hypertrophy, reciprocal interaction between macrophages and T cells to stimulate IFN-γ expression in the heart was reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…The rats were anesthetized by a single intraperitoneal injection of pentobarbital (60 mg/kg), and echocardiography was then performed with VeVo2100 (VisualSonics, Canada). The diastolic intraventricular septum, LV end diastolic diameter, diastolic posterior wall thickness, LV internal dimension in systole, and percent LV fractional shortening were assessed from M-mode images, as previously described [11].…”
Section: Echocardiographymentioning
confidence: 99%